2021
DOI: 10.1111/anu.13348
|View full text |Cite
|
Sign up to set email alerts
|

Effects of betaine supplementation in plant‐protein‐based diets on growth performance, haemato‐immunological parameters, antioxidant status and digestive enzyme activities of juvenile Caspian trout ( Salmo trutta , Kessler, 1877)

Abstract: A feeding trial was conducted to examine the effects of dietary supplementation of betaine on growth performance, haematological-biochemical parameters, antioxidant status and digestive enzyme activities of juvenile Caspian trout, Salmo trutta. A feeding trial was conducted to examine the effects of dietary betaine on growth performance, haematological-immunological parameters, antioxidant defence system and digestive enzyme activities of juvenile Caspian trout, Salmo trutta. For this purpose, 180 juveniles (9… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 53 publications
0
7
0
Order By: Relevance
“…The innate immune system of fish is regarded as the first line of defense against pathogens (Saurabh & Sahoo, 2008), on the other hand, SOD is an antioxidative enzyme that protects against other oxidizing activities that might harm fish (Dröge, 2002). Similarly, inclusion of feed stimulants did not alter FE, chemical composition, hematological parameters, or innate immune response of fish (Hossain et al, 2017;Khosravi et al, 2018;Mohseni et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…The innate immune system of fish is regarded as the first line of defense against pathogens (Saurabh & Sahoo, 2008), on the other hand, SOD is an antioxidative enzyme that protects against other oxidizing activities that might harm fish (Dröge, 2002). Similarly, inclusion of feed stimulants did not alter FE, chemical composition, hematological parameters, or innate immune response of fish (Hossain et al, 2017;Khosravi et al, 2018;Mohseni et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…MDA, a byproduct of lipid peroxidation that can interact with the free amino groups in protein causing cell damage (Xiao et al, 2022), and the contents of MDA in the fish liver can reflect the severity of the free radical attack on the liver or body cells (Całyniuk et al, 2016). Previous studies have demonstrated that limonene, allicin and betaine could improve the antioxidant capacity of fish (Abdel-Tawwab et al, 2021;Dong et al, 2021;Hamed et al, 2021;Ajiboye et al, 2016;Lopes et al, 2019;Lopes et al, 2020;Mohseni et al, 2021). In this study, the GSH and MDA contents variations in the liver as well as the MDA contents in the serum demonstrated the antioxidant effect of the aforesaid three attractants.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to increased feed intake, supplementation of taurine in diets for juvenile whiteleg shrimp has been found to improve growth performance, metabolism, immunity, anti-oxidant capacity, and intestinal health [35][36][37][38][39]. Metabolomic fingerprinting of C. finmarchicus has also revealed that one of its major metabolites is betaine [40], which is a highly soluble glycine derivative with chemoattractive properties for both fish and shrimp [8][9][10][41][42][43]. Alkaline and neutral amino acids, such as glycine, proline, taurine, and valine, and derivatives, like betaine, are known to have chemoattractive properties for olfaction and/or ingestion in carnivorous species [9,10].…”
Section: Feed Intake and Ch/km Inclusion Ratesmentioning
confidence: 99%